Analysis of Conjunctions in the Newspaper of “Bali Travel News” - Sandrianus Sanju; I Gusti Bagus Wahyu Nugraha Putra; I Komang Sulatra (CV Wahana Publikasi, 2024)
This article focused on analyzing the types of conjunctions found in the newspaper Bali Travel News edition May 6-19th, 2022. The data were taken from the Bali Travel News edition of May 6-19th, 2022. This research used an observation approach in the process of collecting the data, first reading the article in the newspaper, then underlining the conjunctions that were found in the article and classifying the conjunctions based on the types of conjunction. This research used the qualitative method to analyze the data. It was started by analyzing the types of conjunctions based on the theory from Halliday and Hassan (1976). The result shows the total of conjunctions found in the article of newspaper 357 data, consist of additive relation with 229 or 64,1% data, adversative relation 10 or 2,8% data, causal relation 106 or 29,7% data, and temporal relation 12 or 3,4% data. The most common conjunctions found in the newspaper of Bali Travel News are additive relations because this type of additional information and correlative conjunctions are really needed when writing an article in the newspaper.